Musle Model Development in Laboratory Studies Using a Rainfall Simulator - Aulia Zahira, Nabila; Andawayanti, Ussy; Suhartanto, Ery; Ramadhani, Rizki (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2024)
Various methods are available for sediment calculation, including the USLE and MUSLE methods, developed based on field observations. For the MUSLE method, it is important to determine the peak flow rate and surface runoff volume. This data is crucial for identifying areas vulnerable to erosion and implementing erosion prevention measures. However, in practice, calculations are often adjusted based on the available data and parameters. This research compares the calculated results of peak flow discharge and surface runoff volume between the Rational Method and the SCS Method with laboratory observations and the applicability of the USLE and MUSLE methods to laboratory sediment observations. Laboratory experiments use a rainfall simulator with intensities of 1 liter/minute, 1.5 liters/minute, and 2 liters/minute, and a maximum land slope of 5%. The research results show that calculating peak flow discharge and surface runoff volume using the Rational Method aligns more closely with laboratory conditions than the SCS Method. However, both methods are considered unsuitable for laboratory observations, as validation calculations and relative error results indicate a mismatch with model performance. Meanwhile, the USLE method is considered more suitable for sediment calculations than the MUSLE method, as the MUSLE method requires adjustment analysis to fit laboratory observations better.